2015
DOI: 10.1016/j.bbmt.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Immunoproteasome Subunit LMP7 with ONX 0914 Ameliorates Graft-versus-Host Disease in an MHC-Matched Minor Histocompatibility Antigen–Disparate Murine Model

Abstract: In the current study we evaluated the effects of immunoproteasome inhibition using ONX 0914 (formerly PR-957) to ameliorate graft-versus-host disease (GVHD). ONX 0914, an LMP7-selective epoxyketone inhibitor of the immunoproteasome, has been shown to reduce cytokine production in activated monocytes and T cells and attenuate disease progression in mouse models of rheumatoid arthritis, colitis, systemic lupus erythematosus, and, more recently, encephalomyelitis. Inhibition of LMP7 with ONX 0914 in the B10.BR→CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(54 reference statements)
0
7
1
Order By: Relevance
“…Interestingly, Zilberberg et al reported LMP7 inhibition to be ef fective in ameliorating graft versus host disease (GvHD) in a miHA disparate murine blood and marrow transplant (BMT) model by de creasing endogenous miHA presentation and consequently reducing allogeneic stimulation and cytokine production (Zilberberg et al, 2015). In contrast to our study, Zilberberg et al used a daily or even 2 x daily treatment regimen, which might have a stronger effect than our treatment strategy.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, Zilberberg et al reported LMP7 inhibition to be ef fective in ameliorating graft versus host disease (GvHD) in a miHA disparate murine blood and marrow transplant (BMT) model by de creasing endogenous miHA presentation and consequently reducing allogeneic stimulation and cytokine production (Zilberberg et al, 2015). In contrast to our study, Zilberberg et al used a daily or even 2 x daily treatment regimen, which might have a stronger effect than our treatment strategy.…”
Section: Discussioncontrasting
confidence: 61%
“…LMP7 inhibition was shown to suppress the differentiation of Th1 and Th17 cells in vitro and in vivo (Muchamuel et al, 2009;Basler et al, 2014;Kalim et al, 2012;Mundt et al, 2016b;Zilberberg et al, 2015). Consequently, the decreased allo specific Th17 differentiation of ONX 0914 treated cells in vitro prompted us to investigate the influence of LMP7 inhibition on allogeneic immune responses in vivo using a murine skin allograft transplantation model.…”
Section: Onx 0914 Treatment Does Not Prolong Graft Survival In An Mhcmentioning
confidence: 99%
“…44 Furthermore, β5i inhibition prevented experimental colitis, 45 Hashimoto thyroiditis, 46 and graft-versus-host disease in an MHC-matched minor histocompatibility antigen-disparate murine model. 47 In addition to providing irreversible proteasome inhibition, carfilzomib displays a distinct, advantageous adverse-event profile compared to bortezomib for the treatment of patients with MM. Understanding of the mechanisms of resistance to proteasome inhibition will not only allow better use of PIs, but may also facilitate rational design of more effective synergistic drug combinations for clinical trials to reduce the BMPCs responsible for alloantibody production.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43] It is notable that the β5i-selective inhibitor ONX0914 has shown to suppress autoreactive immune responses in mouse models of arthritis and diabetes. 47 In addition to providing irreversible proteasome inhibition, carfilzomib displays a distinct, advantageous adverse-event profile compared to bortezomib for the treatment of patients with MM. 47 In addition to providing irreversible proteasome inhibition, carfilzomib displays a distinct, advantageous adverse-event profile compared to bortezomib for the treatment of patients with MM.…”
Section: Cd138 + In Vitro + Cfzmentioning
confidence: 99%
“…The best known function of the iP is its role in antigen processing; however, since astrocytes present little or no antigen [84][85][86], alternate functions of the iP were examined, namely clearance of ROS and oxidatively damaged and poly-ubiquitinated proteins [87]. To determine the role of the iP in astrocyte viability and ROS clearance, we treated regional human astrocytes with or without IFNγ and a specific inhibitor of the iP, ONX 0914 [88][89][90]. Following iP inhibition, an increase in caspase activity was observed only in spinal cord astrocytes compared to media treatment, which was significantly enhanced compared to those from the brainstem (Fig.…”
Section: Ros and Poly-ubiquitinated Protein Accumulation Are Abrogatementioning
confidence: 99%